Non-lethal weapons and their characteristics - Damjanović, Dragan Z. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Non-lethal weapons, also called less-lethal weapons, less-than-lethal weapons, non-deadlyweapons, compliance weapons, or pain-inducing weapons are weapons intended to be less likely to kill a living target than conventional weapons. It is often understood that accidental, incidental, and correlative casualties are risked wherever force is applied, but non-lethal weapons try to minimise the risk as much as possible. Non-lethal weapons are used in combat situations to limit the escalation of conflict where employment of lethal force is prohibited or undesirable, where rules of engagement require minimum casualties, or where policy restricts the use of conventional force. Examples of non-lethal weapons This section is about the weapons and their first application in human history until the modern era. Electronic warfare refers to any action involving the use of the electromagnetic spectrum or directed energy to control the spectrum, attack an enemy, or impede enemy assaults via the spectrum. The purpose of electronic warfare is to deny the opponent the advantage of, and ensure friendly unimpeded access to the EM spectrum. EW can be applied from air, sea, land, and space by manned and unmanned systems, and can target humans, communications, radar, or other assets. EW is employed to support military operations involving various levels of detection, denial, deception, disruption, degradation, protection, and destruction. Conclusion The Centre for Conflict Resolution, Department of Peace Studies, in Bradford created a research project on non-lethal weapons. The project originates back to 1995 and has been functionioning today; its key objectives are a review and description of weapons being developed, identification and tracking of similar and related research institutes involved in the development and production of weapons, testing the impact of non-lethal weapons to international laws, conventions and negotiation weapons, highlighting the ethical and social issues raised in the research, development, implementation and use of such weapons.
Keywords: Weapons; non-lethal weapon; Military; forcing; disadvantages; convents; conventional weapon